Improving Students’ Social Studies Learning Outcomes Using the Group Investigation Model - Mustika Wati; Miftahul Zannah; Ita Rahmiyani; Fauzia Dwi Sasmita (Universitas Lambung Mangkurat, 2023)
This study aims to explore how the group investigation model could be used to improve student learning results in social studies courses. This study was a two-cycle classroom action research study. Six students of class IV from SDN Inti Sungai Miai 11 Banjarmasin participated in this study for the 2020/2021 academic year. Data were collected using observation techniques on implementing lesson plans and student activities and testing on student learning outcomes. The student standard score was ≥ 70, and the expected classical success indicator was 81%-99%. According to the research findings, teacher activity received a score of 90.625 on very good criteria. With practically all active criteria, student activity improved to 85.7%. Individual learning outcomes showed that five students with a classical completeness of 83.33% were nearly entirely complete. Based on these findings, it was possible to conclude that using the Group Investigation model could increase student learning outcomes in social studies courses.